A revised circumscription for the Blakeeae (Melastomataceae) with associated nomenclatural adjustments - Darin Penneys; Walter Judd (PhytoKeys, 2013)
Systematic investigations and phylogenetic analyses of the Blakeeae (Melastomataceae) have indicated that Topobea should be synonymized under Blakea, and Huilaea under Chalybea. Presented here is a detailed description of the Blakeeae, a key to its two accepted genera, and a listing of 62 new combinations, including 3 new names, necessitated by the transfer of Topobea as follows: B. acuminata (Wurdack) Penneys & Judd, comb. nov., B. adscendens (E.Cotton & Matezki) Penneys & Judd, comb. nov., B. albertiae (Wurdack) Penneys & Almeda, comb. nov., B. amplifolia (Almeda) Penneys & Almeda, comb. nov., B. arboricola (Almeda) Penneys & Almeda, comb. nov., B. asplundii (Wurdack) Penneys & Judd, comb. nov., B. barbata (Gleason) Penneys & Judd, comb. nov., B. brenesii (Standl.) Penneys & Almeda, comb. nov., B. brevibractea (Gleason) Penneys & Judd, comb. nov., B. bullata (E.Cotton & Matezki) Penneys & Judd, comb. nov., B. calcarata (L.Uribe) Penneys & Judd, comb. nov., B. calophylla (Almeda) Penneys & Almeda, comb. nov., B. calycularis (Naudin) Penneys & Almeda, comb. nov., B. castanedae (Wurdack) Penneys & Judd, comb. nov., B. clavata (Triana) Penneys & Judd, nom. nov., B. cordata (Gleason) Penneys & Almeda, comb. nov., B. cuprina Penneys & Judd, nom. nov., B. cutucuensis (Wurdack) Penneys & Judd, comb. nov., B. dimorphophylla (Almeda) Penneys & Almeda, comb. nov., B. discolor (Hochr.) Penneys & Judd, comb. nov., B. dodsonorum (Wurdack) Penneys & Almeda, comb. nov., B. eplingii (Wurdack) Penneys & Judd, comb. nov., B. ferruginea (Gleason) Penneys & Judd, comb. nov., B. fragrantissima (Almeda) Penneys & Almeda, comb. nov., B. gerardoana (Almeda) Penneys & Almeda, comb. nov., B. glaberrima (Triana) Penneys & Judd, comb. nov., B. henripittieri (Cogn.) Penneys & Almeda, comb. et nom. nov., B. hexandra (Almeda) Penneys & Almeda, comb. nov., B. horologica Penneys & Judd, nom. nov., B. induta (Markgr.) Penneys & Judd, comb. nov., B. inflata (Triana) Penneys & Judd, comb. nov., B. insignis (Triana) Penneys & Judd, comb. nov., B. intricata (Almeda) Penneys & Almeda, comb. nov., B. killipii (Wurdack) Penneys & Judd, comb. nov., B. lentii (Almeda) Penneys & Almeda, comb. nov., B. longiloba (Wurdack) Penneys & Judd, comb. nov., B. longisepala (Gleason) Penneys & Judd, comb. nov., B. macbrydei (Wurdack) Penneys & Judd, comb. nov., B. maguirei (Wurdack) Penneys & Judd, comb. nov., B. maurofernandeziana (Cogn.) Penneys & Almeda, comb. nov., B. mcphersonii (Almeda) Penneys & Almeda, comb. nov., B. modica (Wurdack) Penneys & Judd, comb. nov., B. mortoniana (Wurdack) Penneys & Judd, comb. nov., B. muricata (Lozano) Penneys & Judd, comb. nov., B. pascoensis (Wurdack) Penneys & Judd, comb. nov., B. pluvialis (Standl.) Penneys & Almeda, comb. nov., B. sessilifolia (Triana) Penneys & Judd, comb. nov., B. setosa (Triana) Penneys & Judd, comb. nov., B. standleyi (L.O.Williams) Penneys & Almeda, comb. nov., B. stephanochaeta (Naudin) Penneys & Judd, comb. nov., B. steyermarkii (Wurdack) Penneys & Judd, comb. nov., B. suaveolens (Almeda) Penneys & Almeda, comb. nov., B. subbarbata (Wurdack) Penneys & Judd, comb. nov., B. subscabrula (Triana) Penneys & Judd, comb. nov., B. subsessiliflora (Wurdack) Penneys & Judd, comb. nov., B. superba (Naudin) Penneys & Judd, comb. nov., B. tetramera (Almeda) Penneys & Almeda, comb. nov., B. tetroici (Wurdack) Penneys & Judd, comb. nov., B. toachiensis (Wurdack) Penneys & Judd, comb. nov., B. trianae (Cogn.) Penneys & Judd, comb. nov., B. verrucosa (Wurdack) Penneys & Judd, comb. nov., B. watsonii (Cogn.) Penneys & Almeda, comb. nov.